(untitled) - Nattinger, James P. (Oxford, 1997)
This book draws on recent language acquisition research to present arguments for a promising new direction in language teaching theory. Part One provides a descriptive account of the lexical phrase and its role in langugae, including discussion of the discourse functions of various types of flexical phrases. Part Two concerns applications for pedagogy, and the final chapter examines important areas for further research, suggesting implications of a lexical phrase approach for various problems in applied linguistics.
Keywords: Language and languages,Phraseology.,Lexicology.,Discourse analysis.,Speech acts ( Linguistics ); Study and teaching